If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(x-3)-3=5x-3(4+x)
We move all terms to the left:
2(x-3)-3-(5x-3(4+x))=0
We add all the numbers together, and all the variables
2(x-3)-(5x-3(x+4))-3=0
We multiply parentheses
2x-(5x-3(x+4))-6-3=0
We calculate terms in parentheses: -(5x-3(x+4)), so:We add all the numbers together, and all the variables
5x-3(x+4)
We multiply parentheses
5x-3x-12
We add all the numbers together, and all the variables
2x-12
Back to the equation:
-(2x-12)
2x-(2x-12)-9=0
We get rid of parentheses
2x-2x+12-9=0
We add all the numbers together, and all the variables
3!=0
There is no solution for this equation
| 3w^+7w=6 | | x2+6x+10=37 | | 2x(4x+-1)=4+2x | | -5v+3=-37 | | 4=2.3^x | | -8-2q=-16 | | 4x+x-5=11x-5x+7 | | x+.35x=30.18 | | -5z-8=-18 | | -3d-1=-13 | | (x/3.9)=(6/11) | | 6-5n=-24 | | 256^x=4 | | 8^x-7=3 | | -5-a=-9 | | X2–4x=-4 | | 5r-5=0 | | -4+a=3 | | 2(z-24)+3(z-3)=28 | | 7/10(x)=42 | | 3(25+.9)m=214 | | -13+43=-5(x+1) | | 2/3h+1=1/3(4h-5) | | 7a+16-39=-4 | | (3x+2)^2+36=0 | | 5x-1-8=180 | | 9z-5z=3z-7+7z | | -42/3=2n/3+7/3+n/3 | | -3+2x=7-3x | | 8/17=a/5 | | n-1/2=n+4/3 | | -3r-4=-7 |